Book Notes [57, Spring 2006] - Finkel, Alvin (Labour / Le Travail, 2006)
The article briefly reviews "Union Women: Forging Feminism in the United Steelworkers of America," by Mary Margaret Fonow, "Women, Power, and AT&T: Winning Rights in the Workplace," by Lois Kathryn Herr, "Reforming the Chicago Teamsters: The Story of Local 705," by Robert Bruno, "The Open Method of Co-ordination in Action: The European Employment and Social Inclusion Strategies," edited by Jonathan Zeitlin and Philippe Pochet, eds., with Lars Magnusson, "Rebuilding Germany: The Creation of the Social Market Economy, 1945-1957," by James C. Van Hook, "Poverty and Charity inthe Jewish Community of Medieval Egypt" and "The Voice of the Poor in the Middle Ages: An Anthology of Documents from the Cairo Geniza," by Mark R. Cohen.
Keywords: BOOKS – Reviews; BRUNO; Robert; FONOW; Mary Margaret; HERR; Lois Kathryn; 1941-; Labor Unions; Nonfiction; REFORMING the Chicago Teamsters: The Story of Local 705 (Book); UNION Women: Forging Feminism in the United Steelworkers of America (Book); WOMEN; Power & AT&T: Winning Rights in the Workplace (Book)